Surface Modification of Commingled Flax/PP and Flax/PLA Fibres by Silane or Atmospheric Argon Plasma Exposure to Improve Fibre–Matrix Adhesion in Composites - Wiwat Pornwannachai; A. Richard Horrocks; Baljinder K. Kandola (Fibers, 2021)
Challenges faced by natural fibre-reinforced composites include poor compatibility between hydrophilic fibres such as flax and hydrophobic polymeric matrices such as polypropylene (PP) or poly(lactic acid) (PLA), and their inherent flammability. The former promotes weak interfacial adhesion between fibre and matrix, which may be further compromised by the addition of a flame retardant. This paper investigates the effect that the added flame retardant (FR), guanylurea methylphosphonate (GUP) and selected surface treatments of commingled flax and either PP or PLA fabrics have on the fibre/matrix interfacial cohesive forces in derived composites. Surface treatments included silanisation and atmospheric plasma flame exposure undertaken both individually and in sequence. 1-, 2- and 8-layered composite laminates were examined for their tensile, peeling and flexural properties, respectively, all of which yield measures of fibre-matrix cohesion. For FR-treated Flax/PP composites, maximum improvement was obtained with the combination of silane (using vinyltriethoxysilane) and plasma (150 W) treatments, with the highest peeling strength and flexural properties. However, for FR-treated Flax/PLA composites, maximum improvement in both properties occurred following 150 W plasma exposure only. The improvements in physical properties were matched by increased fibre-matrix adhesion as shown in SEM images of fractured laminates in which fibre-pullout had been eliminated.